Kaidah Kebahasaan Terkait Praktik Ekonomi Islam - Siswadi, Yudi; Asmuni; Anggraini, Tuti (Jurnal Landraad, 2022)
The Qur'an and Sunnah are the main sources of Islamic law. Islamic law is not only limited as a human abstraction of the reality of society in the occurrence of social order for humans themselves, but rather God's rules for humans. The device to be able to withdraw the law and legal sources is called ijtihad. Allah Subhanahu Wata'ala has revealed the Qur'an in Arabic, as well as the Prophet Muhammad sallallaahu 'alaihi wasallam understood, practiced and gave explanations using Arabic. Thus, one of the most important tools of ijtihad is the rule of law. Related to the economy in the development of science and technology, in the modern era there has been a shift in terms of the form and model of transactions in the financial sector. One side of this change can be seen from the emergence of digital transactions. The development of science and technology has caused several changes in the models and forms of transactions that occur today. These include the presence of bank and non-bank financial institutions, stock exchanges, Islamic financial products, digital transactions and so on. As agreed by the scholars that the Koran and the Sunnah are the main sources of Islamic law. On the other hand, the Quran was revealed in Arabic and its explanations are in Arabic. So one of the important tools that must be mastered by a reviewer of Islamic law is the mastery of the rules of the Arabic language.